Comparison of Cartesian and radial acquisition on short-tau inversion recovery (STIR) sequences in breast MRI - Santucci, Domiziana (Radiol Bras, 2017)
OBJECTIVE: The purpose of this study was to compare two short-tau inversion recovery (STIR) sequences, Cartesian and radial (BLADE) acquisitions, for breast magnetic resonance imaging (MRI) examinations. MATERIALS AND METHODS: Ninety-six women underwent 1.5 T breast MRI exam (48 Cartesian and 48 BLADE). Qualitative analysis including image artifacts, image quality, fat-suppression, chest-wall depiction, lesion detection, lymph node depiction and overall impression were evaluated by three blinded readers. Signal to noise ratios (SNRs) were calculated. Cronbach's alpha test was used to assess inter-observer agreement. Subanalyses of image quality, chest-wall depiction and overall impression in 15 patients with implants and image quality in 31 patients with clips were correlated using Pearson test. Wilcoxon rank sum test and t-test were performed. RESULTS: Motion artifacts were present in 100% and in 0% of the Cartesian and the BLADE exams, respectively. Chemical-shift artifacts were present in 8% of the Cartesian exams. Flow artifacts were more frequent on BLADE. BLADE sequence was statistically superior to Cartesian for all qualitative features (p < 0.05) except for fat-suppression (p = 0.054). In the subanalysis, BLADE was superior for implants and clips (p < 0.05). SNR was statistically greater for BLADE (48.35 vs. 16.17). Cronbach ranged from 0.502 to 0.813. CONCLUSION: BLADE appears to be superior to Cartesian acquisition of STIR imaging as measured by improved image quality, fewer artifacts, and improved chest wall and lymph node depiction.